Beyond the Lamppost: A Proposal for a Fourth Wave of Education for Collaboration. (October 2018) - Paradis, Elise; Whitehead, Cynthia R.
Abstract : Interprofessional education (IPE) is an increasingly popular educational model that aims to educate health care students to be better collaborators by enabling them to learn with, from, and about each other. IPE's rising popularity is evident in the increase in scholarship on this topic over the last few decades. In this Perspective, the authors briefly describe three historical "waves" of IPE: managing the health workforce through shared curriculum, maximizing population health through health workforce planning, and fixing individuals to fix health care. Using insights from the social sciences and past practice, they then discuss six reasons why the current third wave of IPE is likely to fall short of meeting its goals, including that (1) IPE is logistically complex and costly, (2) IPE is developmentally inappropriate, (3) the link between IPE and key outcomes is still missing, (4) IPE insufficiently engages with theory, (5) IPE rarely addresses power and conflict, and (6) health care is an inertial system that IPE is unlikely to change. The authors conclude by sharing their vision for a fourth wave of education for collaboration, addressing workplace systems and structures, which would combine undergraduate, uniprofessional education for collaboration with practice-based interventions.